Nexus of Knowledge Transfer, Green Innovation and Environmental Performance: Impact of Environmental Management Accounting - Zandi, Gholam Reza; Khalid, Nadeem; Islam, Dewan Md. Zahurul (International Journal of Energy Economics and Policy, 2019)
The present study is motivated to investigate the importance of ecological innovations and knowledge management in influencing environmental performance. The focus of the present study lies in identifying the contribution of environmental management accounting in driving the firm’s knowledge transfer, green innovation, and environmental performance in Indonesian small and medium enterprises sector. The current collected the data from 223 respondents from different SMEs of Indonesia. The results of PLS-SEM confirm that all variables have a positive and significant impact on the environmental performance of Indonesia SMEs. Moreover, the outcomes of the PLS-SEM confirm that knowledge transfer, green innovation, and environmental performance have significantly and positively impacted by environmental management accounting system. The outcomes of partial least square structural equation modelling also indicate that knowledge transfer and green innovation have also positively and significantly impact on the environmental performance. The results further recommended that the firms can improve their environmental performance by implementing good environmental management accounting system. Keywords: Knowledge transfer, green innovation, environmental performance, Indonesia. JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8285